2019
DOI: 10.1186/s12912-019-0378-3
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ perceptions and experiences of autonomy: a descriptive phenomenological study

Abstract: BackgroundProfessional autonomy is a key concept in understanding nurses’ roles in delivering patient care. Recent research exploring the role of autonomy in the nursing work environment indicated that English and American nurses had differing perceptions of autonomy. This qualitative study aimed to explore the understanding and experiences of autonomy of nurses working in England.MethodsA descriptive phenomenological analysis of data from 48 semi-structured interviews with registered nurses from two National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 30 publications
(38 reference statements)
8
36
0
4
Order By: Relevance
“…The many interruptions we observed from other HPs may well be an indication of this hierarchy, implying, as it did, a lack of respect for and acknowledgment of nursing and RNs' time and independent role and function. This nding is supported by previous research [33,[38][39][40][41] indicating that the hierarchy has an impact on evidence-based nursing practice and that RNs experience a lack of support from physicians as well as interdisciplinary awareness of the value and impact of evidence-based NC [41,42]. It is important to emphasise that this pattern found in our study did not appear to be based on conscious actions or foul intentions from other professionals; rather, it was a barrier embedded in the organisational culture by tradition, poor leadership, and lack of societal and professional acknowledgment of the value and impact of nursing.…”
Section: Team-based and Organisational Barriers And Facilitatorssupporting
confidence: 87%
“…The many interruptions we observed from other HPs may well be an indication of this hierarchy, implying, as it did, a lack of respect for and acknowledgment of nursing and RNs' time and independent role and function. This nding is supported by previous research [33,[38][39][40][41] indicating that the hierarchy has an impact on evidence-based nursing practice and that RNs experience a lack of support from physicians as well as interdisciplinary awareness of the value and impact of evidence-based NC [41,42]. It is important to emphasise that this pattern found in our study did not appear to be based on conscious actions or foul intentions from other professionals; rather, it was a barrier embedded in the organisational culture by tradition, poor leadership, and lack of societal and professional acknowledgment of the value and impact of nursing.…”
Section: Team-based and Organisational Barriers And Facilitatorssupporting
confidence: 87%
“…A study carried out with nurses from England revealed that some nurses are able to exercise their autonomy through teamwork, in their daily practices sharing their knowledge and skills. Thus, nurses reported that the hierarchy of health systems, as well as policies and guidelines, are determinant for their performance in an autonomous manner, 19 which is essential for their motivation and satisfaction in the context of the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Pētnieki norāda, ka praktizējošo māsu izlasē trūkst vienprātības par autonomijas jēdzienu. Tiek norādīts, ka nav noteiktas autonomijas definīcijas, un konstatēta autonomijas interpretācijas dažādība (Oshodi et al, 2019). Savukārt pētījumā " Patient Participation in Decision Making During Nursing Care in Greece -A Comparative Study" secināts, ka pacientu līdzdalība, lai arī mērena, bija acīm redzama slimnīcas apstākļos.…”
Section: Autonomijas Princips ķIrurģiskās Aprūpes Māsas Praksēunclassified